2005
DOI: 10.1111/j.1600-051x.2005.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Brushing with and without dentifrice on gingival abrasion

Abstract: No statistically significant difference in the incidence of gingival abrasion was found between brushing with dentifrice or without dentifrice. Neither did oral sensory perception seem to affect the incidence of gingival abrasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 18 publications
2
25
0
1
Order By: Relevance
“…People brush their teeth to feel fresh and confident, have a nice smile, avoid bad breath and avoid disease [2]. A toothbrush is one of the most familiar devices of everyday use and few people would ever think about its associated risks [3].…”
Section: Introductionmentioning
confidence: 99%
“…People brush their teeth to feel fresh and confident, have a nice smile, avoid bad breath and avoid disease [2]. A toothbrush is one of the most familiar devices of everyday use and few people would ever think about its associated risks [3].…”
Section: Introductionmentioning
confidence: 99%
“…Versteeg et al . (2005) showed that there was no difference in GAs between participants who brushed their own teeth (with their own sensory perception feedback) and those whose teeth were brushed by a professional brusher. The most probable explanation for the effect size difference between the present study and Rosema et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, Versteeg et al . (2005) observed that the use of a dentifrice, with its abrasive ingredients and detergents, did not induce additional abrasions. This observation was in agreement with earlier work by Alexander et al .…”
Section: Discussionmentioning
confidence: 99%
“…23 Moreover, the abrasive dentifrice components (silica, alumina, calcium carbonate), which are related to a dentifrice's degree of abrasiveness, can cause mechanical abrasion of the epithelium. According to Verteeg et al, 24 brushing with a dentifrice did not result in increased gingival abrasion. Our results partially agree with those of these authors, since the use of a dentifrice resulted in a significant increase in lesions at specific locations (buccal and lingual surfaces of the free gingiva).…”
Section: Discussionmentioning
confidence: 99%
“…25 RDA is important, as abrasive toothpastes can aggravate brush-induced gingival abrasion. Versteeg et al 24 used a dentifrice with an RDA of ± 77. In the present study, a dentifrice with a greater abrasiveness (RDA ± 160) was used.…”
Section: Discussionmentioning
confidence: 99%